1992
DOI: 10.1093/oxfordjournals.jbchem.a123791
|View full text |Cite
|
Sign up to set email alerts
|

1H-NMR Assignment and Secondary Structure of Human Insulin-Like Growth Factor-I(IGF-I) in Solution

Abstract: Human insulin-like growth factor-I (IGF-I) was studied by two-dimensional 1H-NMR spectroscopy. Resonance assignments were obtained for all the backbone protons and almost all of the sidechain protons of the total 70 amino acid residues, using sequence-specific assignment procedures. The secondary structure elements of human IGF-I were identified by investigation of the sequential and medium range NOEs as a preliminary step in determining the three-dimensional structure of this protein by means of distance geom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
30
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 0 publications
5
30
0
Order By: Relevance
“…Others have reduced the IGF-I self-association at 2-10 mM protein concentration, and thereby improved the spectral quality, by the addition of 10% (8) or 20% (9) acetic acid. In this study, we have not used acetic acid, since it influences the IGF-I/IGFBP-1 binding affinity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Others have reduced the IGF-I self-association at 2-10 mM protein concentration, and thereby improved the spectral quality, by the addition of 10% (8) or 20% (9) acetic acid. In this study, we have not used acetic acid, since it influences the IGF-I/IGFBP-1 binding affinity.…”
Section: Resultsmentioning
confidence: 99%
“…No assignments whatsoever could be made for residues 18, 34 -37, 50, 63, 68, and 69 in that study. For the studies performed with acetic acid present (6,8), virtually complete assignments were accomplished.…”
Section: Resultsmentioning
confidence: 99%
“…The number of restraints used in the refinement of the structure of Long-[Arg 3 ]IGF-I is significantly greater than used for the original IGF-I structures (9,10) and is comparable to the number used for subsequent work with IGF-II (13) and analogs of IGF-I (25,26). The solution structures of Long- [Arg 3 ]IGF-I display good convergence to a single fold in the hydrophobic core region containing the three ␣-helices (Fig.…”
Section: Structure Determination Of Long-[arg 3 ]Igf-i-mentioning
confidence: 99%
“…Recent NMR studies have revealed that IGF-I has three ␣-helical regions surrounding a hydrophobic core (9,10). Residues 3-29 of IGF-I, which are homologous to the B-chain of insulin, contain helix-1 (Ala 8 to Cys 18 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation